Talazoparib has no clinically relevant effect on QTc interval in patients with advanced solid tumors. Issue 5 (June 2019) - Hoffman, Justin; Chakrabarti, Jayeta; Plotka, Anna; Milillo Naraine, Adriana; Kanamori, David; Moroose, Rebecca; Nguyen, Linh; Wang, Diane; Wainberg, Zev A.
Abstract : The aims of this study were (i) to evaluate the effect of talazoparib (1 mg once daily) on cardiac repolarization in patients with advanced solid tumors by assessing corrected QT interval (QTc) and (ii) to examine the relationship between plasma talazoparib concentration and QTc. In this open-label phase 1 study, patients had continuous 12-lead ECG recordings at baseline followed by time-matched continuous ECG recordings and collection of talazoparib plasma pharmacokinetic samples predose and at 1, 2, 4, and 6 h postdose on treatment days 1 and 22 and before talazoparib administration on day 2. ECG recordings were submitted for independent central review where triplicate 10-s ECGs, extracted up to 15 min before pharmacokinetic samples, were assessed for RR, PR, QRS, and QT intervals and ECG morphology. QT interval was corrected for heart rate using Fridericia's (QTcF) and Bazett's (QTcB) formulae. Linear mixed-effects modeling was used to examine the relationship between QTc and RR interval change from baseline and plasma talazoparib concentration. Thirty-seven patients received talazoparib. Mean change in QTcF from time-matched baseline ranged from −3.5 to 6.9 ms, with the greatest change 1 h postdose on day 22. No clinically relevant changes in PR, QRS, QTcB, QTcF, or RR intervals, heart rate, or ECG morphology were observed. No concentration-dependent effect on heart rate or QTc was observed. No deaths, permanent treatment discontinuations due to adverse events were reported. Talazoparib (1 mg once daily) had no clinically relevant effects on cardiac repolarization. Abstract : Supplemental Digital Content is available in the text.